2023
DOI: 10.1002/smll.202302492
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Direct X‐Ray Detector Based on Copper(II) Coordination Polymer Single Crystal with Anisotropic Charge Transport

Abstract: Anisotropic charge transport plays a pivotal role in clarifying the conductivity mechanism in direct X‐ray detection to improve the detection sensitivity. However, the anisotropic photoelectric effect of semiconductive single crystal responsive to X‐ray is still lacking of theoretical and experimental proof. The semiconductive coordination polymers (CPs) with designable structures, adjustable functions, and high crystallinity provide a suitable platform for exploring the anisotropic conductive mechanism. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The solvent-based approach for ECCs synthesis entails breaking the ionic bonds in inorganic salts and subsequently reassembling them with organic ligands to create coordination compounds. 18,19 While generally feasible, this process can become intricate, primarily due to solvent involvement (Scheme 1, Path 1). One prevalent issue is the potential introduction of solvent molecules that are challenging to remove into the resulting ECCs, including coordinated or crystallization water.…”
Section: Introductionmentioning
confidence: 99%
“…The solvent-based approach for ECCs synthesis entails breaking the ionic bonds in inorganic salts and subsequently reassembling them with organic ligands to create coordination compounds. 18,19 While generally feasible, this process can become intricate, primarily due to solvent involvement (Scheme 1, Path 1). One prevalent issue is the potential introduction of solvent molecules that are challenging to remove into the resulting ECCs, including coordinated or crystallization water.…”
Section: Introductionmentioning
confidence: 99%
“…22 A polycrystalline pellet sample of this Tb( iii )–benzoquinone MOF had a thermal stability up to 200 °C and an X-ray sensitivity of 23.8 μC Gy −1 cm −2 under 80 kV p X-ray exposure, and is competitive with the commercial a-Se detector. Guo, Zheng and coworkers found that a single-crystal detector of a copper( ii ) MOF 23 displayed a superior sensitivity of 2697.15 μC Gy −1 cm −2 . In 2022, Han et al reported a viologen-templated zinc-oxalate semiconductive MOF (EV-MOF detector) with the highest X-ray sensitivity (3216 μC Gy −1 cm −2 at 1339 V cm −1 ) so far.…”
Section: Introductionmentioning
confidence: 99%